Relations among personal initiative and the development of reading strategy knowledge and reading comprehension - Warner, Greta J.; Fay, Doris; Spörer, Nadine (Frontline Learning Research, 2017)
Reading comprehension is a self-regulated activity that depends on the proactive effort of the reader. Therefore, the authors studied the effects of personal initiative (PI) on the development of reading comprehension, mediated by reading strategy knowledge. Structural equation modelling was applied to a longitudinal study with two data waves separated by two years. At Time 1, the participants (N = 1,102) were either in third or fourth grade. At Time 2, third graders had moved to grade five, and fourth graders had moved to grade six (N = 1,009). At both grade levels, PI explained unique variance in reading strategy knowledge and reading comprehension at Time 2. Moreover, from fourth to sixth grade the effect of PI on reading comprehension was mediated by reading strategy knowledge. No mediation was observed from third to fifth grade. These findings emphasize the relevance of PI in the development of reading strategy knowledge and reading comprehension. They further reveal that the hypothesized mediation process does not unfold until sixth grade.